2012
DOI: 10.17221/26/2011-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the development of Phytophthora alni ssp. alni infections in Alnus glutinosa L.

Abstract: Phytophthora alni is responsible for a devastating disease in alder and changes in the environment of riparian and alder carr ecosystems. One of the main approaches to solve this problem is to find naturally resistant genotypes using a series of artificial inoculation experiments, to preserve and use them in programmes for resistance breeding. However, the results of artificial inoculation experiments (screening for natural resistance) can be affected by several factors. The potential effect of the social stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The results of infection of alder with P. alni complex depend on several factors: type of inoculated organ [40,41], method of inoculation [40], environment condition [42], derivation of isolate-host genotype, geographic provenience [37], and, as was shown in our study, from what source the isolates were obtained-diseased trunks or soil from under these trees.…”
Section: Discussionmentioning
confidence: 52%
“…The results of infection of alder with P. alni complex depend on several factors: type of inoculated organ [40,41], method of inoculation [40], environment condition [42], derivation of isolate-host genotype, geographic provenience [37], and, as was shown in our study, from what source the isolates were obtained-diseased trunks or soil from under these trees.…”
Section: Discussionmentioning
confidence: 52%
“…Re‐isolations of the pathogen from necroses were consistently successful in a series of inoculations in a pretest, which was partially published in Štochlová et al. (). As carrying out this number of re‐isolations in the main test would be highly time‐consuming, the success of infections was checked visually by noting the presence or absence of necroses in comparison with the controls.…”
Section: Methodsmentioning
confidence: 91%
“…The flasks were then placed in randomized positions in an incubator at 20°C and incubated for 1 week in the dark (Štochlová et al. ). After the incubation period, the segments were quick‐frozen to stop pathogen development (Černý et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wound inoculation, either on detached or in situ stems, has been used to test seasonal changes in susceptibility of black alder to P. × alni (Stochlová et al ., ) and of red oaks to P. cinnamomi (Robin et al ., ). In agreement with these studies, the present investigation showed that the highest susceptibility was in summer.…”
Section: Discussionmentioning
confidence: 99%